Should therapy-related myeloid leukemia be treated like de novo acute myeloid leukemia? (Hematology Meeting Reports, 2009)
The diagnosis of therapy-related myeloid leukemia (t-MDS/t-AML) identifies a group of high-risk patients with multiple and varied poor prognostic features. Their outcomes have historically been poor compared to people who develop AML de novo. The question arises whether a diagnosis of t-AML per se indicates a poor prognosis, or whether their bad outcomes result from certain clinical and biologic characteristics. Because of lingering damage from prior cytotoxic therapy and in some cases the persistence of their primary disorder, t-AML patients are often poor candidate for intensive AML therapy. The spectrum of cytogenetic abnormalities in t-AML is similar to de novo AML, but the frequency of unfavorable cytogenetics, such as a complex karyotype or deletion or loss of chromosomes 5 and/or 7, is higher in t-AML. Survival varies according to cytogenetic risk group, with better outcomes observed in t-AML patients with favorable-risk karyotypes. Treatment recommendations should be based on performance status and karyotype. Patients with t-AML should be enrolled on front-line chemotherapy trials, appropriate for de novo AML patients with similar disease characteristics. Allogeneic hematopoietic cell transplantation can cure some t-AML patients. Most importantly, the molecular and genetic differences that appear to determine the phenotype and the outcome of these patients need to be investigated further.